2022
DOI: 10.1111/1460-6984.12830
|View full text |Cite
|
Sign up to set email alerts
|

Scandcleft randomized trials of primary surgery for unilateral cleft lip and palate: Speech proficiency at 10 years of age

Abstract: Background & Aim: To assess consonant proficiency and velopharyngeal function in 10-year-old children born with unilateral cleft lip and palate (UCLP) within the Scandcleft project. Methods & Procedures: Three parallel group, randomized, clinical trials were undertaken as an international multicentre study by nine cleft teams in five countries. Three different surgical protocols for primary palate repair (Arm B-Lip and soft palate closure at 3-4 months, hard palate closure at 36 months, Arm C-Lip closure at 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 83 publications
1
7
1
Order By: Relevance
“…Aspects other than surgery and speech function might add to the understanding of what affects speech outcomes. 25 In conclusion, it is possible to affirm that these preliminary speech outcomes are similar to previous studies, regardless of surgical protocol.…”
Section: Vpc-rates Per Surgeon (N) Vpc Indicates Velopharyngeal Compe...supporting
confidence: 83%
See 1 more Smart Citation
“…Aspects other than surgery and speech function might add to the understanding of what affects speech outcomes. 25 In conclusion, it is possible to affirm that these preliminary speech outcomes are similar to previous studies, regardless of surgical protocol.…”
Section: Vpc-rates Per Surgeon (N) Vpc Indicates Velopharyngeal Compe...supporting
confidence: 83%
“…Previous studies have examined speech outcomes and the relationship with surgical intervention in 5 year olds. Aspects other than surgery and speech function might add to the understanding of what affects speech outcomes 25 …”
Section: Discussionmentioning
confidence: 99%
“…Several of the included studies were RCTs (28)(29)(30)(31)(34)(35)(36)(37)(38)(39) but understandably had to use unblinded operators, which inherently increases the risk of performance bias. This is a weakness that is difficult to avoid when conducting research on surgical techniques and outcomes, as it is impossible to use blinded surgeons and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Speech outcomes were reported in four original studies. Two of these were RCTs within the Scandcleft trials (34,35), one was a subgroup analysis within the Scandcleft trials (36), and one was an independent RCT (37). In all the studies, speech was evaluated through perceptual speech assessment.…”
Section: Outcome O2: Speechmentioning
confidence: 99%
“…No significant differences in velopharyngeal competency (evaluated with the composite variable VPC-sum) and hypernasality were found [10]. At 10 years of age, the results indicated that children treated with two-stage closure with hard palate closure at 36 months had lower PCC than children treated with simultaneous hard and soft palate closure at 12 months of age, whereas the proportion of children with primary VPC (without secondary surgery to improve function) was higher in the group with delayed hard palate closure [11]. A national survey from New Zealand included 56 children with cleft lip and palate at 10 years of age and found adequate velopharyngeal function in 66% and a need for further investigation or therapy in 25% [12].…”
Section: Introductionmentioning
confidence: 98%